Malaysian Tourism Marketing and Promotion a Comparative Study - Nair, Mohanan (1997)
Malaysia' tourism sector has everything going for it. It has a good tourism infrastructure over the last decade, capital city Kuala Lumpur and the various principal towns of Penang, Malacca, Kuantan and Johor Bahru have rapidly developed into modern, thriving metropolises. The road system l inking the Peninsular's northern and southern state, east and west coasts is excellent. Its electronic and media communication is excellent. Malaysia can proudly say that it has got some of the region's finest hotels and resorts. Despite the successful conclusion of Visit Malaysia Year 1990, Malaysia is still a long way from being a top of mind destination to retain its fragile hold on the fleeting and fickle-minded travelling public, the country's tourism promoters will have to zealously continue targetted and sustained promotional activities. The study examines the marketing and promotional activities carried out by the Malaysian Tourism Promotional Board (MTPB) and the New Zealand Tourism Board (NZTB). NZTB is chosen because of its long involvement in tourism. The first chapter deals with an overview of tourism in Malaysia. It shows the importance of tourism to the Malaysian economy. Tourism Policy is discussed in second chapter. Chapter three discusses the marketing strategies employed by MTPB. Promotional programmes are discussed in Chapter five. An overview of Tourism in New Zealand is discussed in Chapter six. Chapter seven deals with marketing New Zealand as a visitor destination. Market Reasearch is discussed in Chapter eight. SWOT analysis is carried out in Chapter nine. Conclusion and recommendations are discussed in Chapter ten.